ANALYZE FACTORS INFLUENCING WORK COMMITMENT FROM ISLAMIC PERSPECTIVES AMONG CIVIL SERVANTS - Othman, Azizah; Tahir, Raziah Md; Yusof, Syarifah Md (CENTRAL ASIA AND THE CAUCASUS, 2021)
Various efforts have been made by the government to ensure that civil servants are committed to providing the best service. Although various efforts have been introduced by the government in the effort to improve the services of civil servants, there are still many negative issues raised concerning their services. Therefore, the objective of this study is to examine the relationship and influence of intrinsic reward, extrinsic reward, role conflict, role overload, and work satisfaction on the work commitment. The final aim is to explore how these factors can affect the work commitment of civil servants. This research uses quantitative methods to meet the objectives of the study. The statistical results of the multiple regression analysis found that extrinsic reward, role conflict, and work satisfaction significantly affect job commitment while intrinsic reward and role overload did not affect the work commitment. In other words, work satisfaction is the most important factor in increasing the work commitment, followed by extrinsic reward and role conflict. Meanwhile, intrinsic reward and role overload are not proven to be important in influencing work commitments.